Killer instinct - Barnes, Jennifer (Jennifer Lynn) (Barnes, Jennifer (Jennifer Lynn). Naturals novel., 2014)
"Friendship. Romance. Serial killers. The Naturals are on the case. Seventeen-year-old Cassie Hobbes has a gift for profiling people. Her talent has landed her a spot in an elite FBI program for teens with innate crime-solving abilities, and into some harrowing situations. After barely escaping a confrontation with an unbalanced killer obsessed with her mother's murder, Cassie hopes she and the rest of the team can stick to solving cold cases from a distance. But when victims of a brutal new serial killer start turning up, the Naturals are pulled into an active case that strikes too close to home: the killer is a perfect copycat of Dean's incarcerated father -- a man he'd do anything to forget. Forced deeper into a murderer's psyche than ever before, will the Naturals be able to outsmart the enigmatic killer's brutal mind games before this copycat twists them into his web for good?"--